Impiego sperimentale del drone ad ala fissa nell'elaborazione dell'indice di qualità morfologica (IQM) dei corpi idrici - Stella, Fabrizio; Bassan, Rodolfo; Cavinato, Antonio; Lusiani, Giovanni (GEOmedia, 2017)
The directive 2000/60/EC (EU Water Framework Directive) provides procedures for identifying the ecological status of each water body by considering the quality of the biological community and the hydrological and chemical characteristics of the water body itself. However, in mountain areas the hydromorphological index can be hard to determine due to poor accessibility of measurement sites and lacking photogrammetric coverage. In order to guarantee safety of the operators and, at the same time, precise calculations in a short amount of time, the use of a fixed wing drone is proposed. A preliminary test was performed in the upper segment of ‘Val del Grisol' in the Dolomites of Belluno by ARPAV – Belluno Department and AVEPA, obtaining high-quality, geo-referenced photogrammetric images.